Analisis Tingkat Kompleksitas Waktu dan Tingkat Keamanan Enkripsi Pada Algoritma Kriptografi RSA, DES, AES - Muhamad Zulfikar; Tapha Imanuddin; Riyan Anugrah Alhad; Nova Eko Prastyo; Satriya Adi Firmansyah (JURNAL SITEBA, 2023)
In today's era of advanced information and technology, data plays an important role. However, the importance of data also brings challenges in terms of security and privacy. Cryptography is an effective solution to maintain data security by encoding information so that only authorized parties can read it. This research aims to compare cryptography algorithms such as RSA, DES, AES. This comparison will give an idea about the security level of each algorithm in various situations. RSA is a strong public key cryptography algorithm, using large number factorization for its security. RSA encryption requires O(n^k) time complexity, where n is the number of bits in the public key and k corresponds to the factorization algorithm. The longer the key, the higher the security level, but the encryption process can be slower. DES is a symmetric key cryptography algorithm with 64-bit blocks and O(1) time complexity in the encryption process. However, the relatively short key length makes DES vulnerable to brute-force attacks. AES is a symmetric key cryptography algorithm with 128-bit blocks and 128-bit keys. The AES encryption process has O(1) time complexity, offers better security with longer key sizes and complex structures, and reduces the risk of brute-force attacks. AES is a highly secure and efficient encryption algorithm for maintaining data confidentiality and integrity.